Health Care Workers' Adherence to Hand Hygiene Guidelines in Emergency Surgical Room of a Tertiary Care Hospital - Dhamnaskar, Suchin Sudhakar; Chaudhari, Gautami Milind; Koranne, Mandar Sharadchandra (The Surgery Journal, 2022)
Background Out of every 100 hospitalized patients, 7 patients in advanced countries and 10 patients in emerging countries acquire health care-associated infections (HCAIs). Hand hygiene (HH) procedures are the simple and cost-effective solution to significantly reduce HCAI. We wanted to know the compliance rate of HH procedures among health care workers (HCWs) working in emergency surgical room (ESR) of our institute, so that feedback can be given to them and further interventions can be planned.Methodology This is a cross-sectional observational study conducted in ESR. Resident doctors and faculties, interns, and nurses were directly observed for all the five moments of HH recommended by World Health Organization (WHO). The data have been recorded with the WHO recommended form for observation and basic compliance calculation for HH.Results In total, 1,370 HH opportunities were observed and recorded, of which 690 were for resident doctors and faculties, and 340 each for interns and nurses. The overall total HH compliance rate among all HCWs was 41.3% and resident doctors and faculties had the poorest compliance. Poorest compliance was observed for moment 1, whereas maximum compliance was for moment 3 among all the HCWs.Conclusion HCWs' adherence to HH guidelines in ESR of this tertiary care hospital is low and is least in resident doctors and faculties.
Keywords: hand hygiene moments; compliance; emergency surgical room